1979
DOI: 10.1111/j.1095-8649.1979.tb03680.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of dissolved oxygen and salinity on the toxicity of ammonia to smolts of salmon, Salmo salar L.

Abstract: The survival of Atlantic salmon srnolts on exposure to constant concentrations of ammonia has been measured under laboratory conditions. At concentrations of dissolved oxygen close to the air-saturation value, the 24-h LC50 of un-ionised ammonia is 0.15 mg NH, 1 -I in fresh water (hardness 264 mg I-' as CaCO,) and 0.3 mg NH,I-l in 30% sea water; at concentrations of dissolved oxygen of 3.5 mg 1-i in fresh water and 3.1 mg 1 -I in 30% sea water, the 24-h LC50 is 0.09 mg NH, 1-1 and 0.12 mg NH, 1-1 respectively;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0
2

Year Published

1990
1990
2004
2004

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(37 citation statements)
references
References 16 publications
1
34
0
2
Order By: Relevance
“…Ammonia is acutely toxic between 0.09 and 3.35 mg 1-1 as NH3-N in seawater for the few species that have been investigated (Table 1). Toxicity is also dependent on salinity, temperature, and water pH (Hazel et al, 1971;Alabaster et al, 1979Alabaster et al, , 1983Alderson, 1979;Miller et al, 1990;Soderberg and Meade, 1991;Wajsbrot et al, 1991).…”
Section: Ammonia Toxicitymentioning
confidence: 99%
See 2 more Smart Citations
“…Ammonia is acutely toxic between 0.09 and 3.35 mg 1-1 as NH3-N in seawater for the few species that have been investigated (Table 1). Toxicity is also dependent on salinity, temperature, and water pH (Hazel et al, 1971;Alabaster et al, 1979Alabaster et al, , 1983Alderson, 1979;Miller et al, 1990;Soderberg and Meade, 1991;Wajsbrot et al, 1991).…”
Section: Ammonia Toxicitymentioning
confidence: 99%
“…Alabaster et al (1979) reported 24 h LCs0 for Atlantic salmon of 0.09 and 0.23 mg 1 -I NH3-N at DO levels of 3.1 and 9.5 mg 1-1 respectively; thus the risk of ammonia toxicity may be minimized with DO > 10 mg 1-1 in seawater. Ammonia toxicity is ameliorated at acidic pH values in freshwater (Russo and Thurston, 1991), but the pH effect in seawater is unclear.…”
Section: Ammonia Toxicitymentioning
confidence: 99%
See 1 more Smart Citation
“…Alabaster et al, 1979;Hamm, 1991;Haywood, 1983;Hvitved-Jacobsen, 1982;Jacob et al, 1984;Russo & Thurston, 1977) were taken into account additionally. The data stock was completed by our investigations (Podraza et al, 2002) with fry released into the water upstream and downstream of the discharge points.…”
Section: Evaluation Of Threshold Concentrations For the Receiving Watermentioning
confidence: 99%
“…The percent of total ammonia present in the unionized form is significantly affected by factors such as pH, temperature, and to a lesser degree the ionic strength of the solution (e.g. hardness or salinity) (Thurston et al 1981b, Alabaster et al 1979, Emerson et al 1975, Whitfield 1974, Skarheim 1973.…”
Section: Noncontaminant-related Toxicity Potentialmentioning
confidence: 99%